Prognostic importance of progesterone receptor expression in meningioma (Annals of Medical Research, 2021)
Aim: : In this study, our objective was to demonstrate the relationship of progesterone receptor (PR) expression with histological grade and other prognostic factors in patients with meningiomas. Material and Methods: Brain biopsy materials, which were examined and diagnosed with meningioma between January 2011 and January 2015, were screened in a retrospective study design. Ninety-six of the cases, who were diagnosed with meningioma with a grade of I, II, and III according to WHO and had undergone immunohistochemically PR expression, were included in the study.Results: JThere was a weak correlation between WHO grade and PR expression rate and intensity in our study. PR expression rate and intensity showed increment as the grade progressed. On the other hand, there was no correlation of PR expression rate and intensity with other prognostic parameters such as Ki67 proliferation index and mitotic index. Conclusion: Although we have detected a weak correlation between PR expression rate and intensity with WHO grade, we think that PR expression rate and intensity do not have prognostic role in the meningiomas due to the absence of a similar relationship between other important parameters in prognosis. In most of the studies in the literature, it is reported that PR expression rate and intensity decreases with increasing WHO grade. However, the number of studies with the opposite results is high. In the presence of conflicting data in the literature and considering that almost all of these studies were performed according to the WHO classification before 2016 (before the new WHO classification), we concluded that further multi-centre studies utilizing new classification system and have more homogeneous distribution of the grades are required to investigate the relationship between PR and histopathologic grade and other prognostic parameters.
Keywords: Meningioma; progesterone receptor; prognostic factors